Microtubule Organizing Centers Contain Testis-Specific γ-TuRC Proteins in Spermatids of Drosophila - Alzyoud, Elham; Vedelek, Viktor; Réthi-Nagy, Zsuzsánna; Lipinszki, Zoltán; Sinka, Rita (Frontiers in Cell and Developmental Biology, 2021)
Microtubule nucleation in eukaryotes is primarily promoted by γ-tubulin and the evolutionary conserved protein complex, γ-Tubulin Ring Complex (γ-TuRC). γ-TuRC is part of the centrosome and basal body, which are the best-known microtubule-organizing centers. Centrosomes undergo intensive and dynamic changes during spermatogenesis, as they turn into basal bodies, a prerequisite for axoneme formation during spermatogenesis. We described the existence of a novel, tissue-specific γ TuRC in Drosophila. We characterize three genes encoding testis-specific components of γ TuRC (t-γ-TuRC) and find that presence of t-γ-TuRC is essential to male fertility. We show the diverse subcellular distribution of the t-γ-TuRC proteins during post-meiotic development, at first at the centriole adjunct and then also on the anterior tip of the nucleus, and finally, they appear in the tail region, close to the mitochondria. We also proved the physical interactions between the t-γ-TuRC members, γ-tubulin and Mozart1. Our results further indicate heterogeneity in γ-TuRC composition during spermatogenesis and suggest that the different post-meiotic microtubule organizing centers are orchestrated by testis-specific gene products, including t-γ-TuRC.